Prospective comparative study of the use prp and viscoelastic sodium hyaluronate gel in patients with grade ii knee osteoarthritis - Gulnazarova, Stella; Isakova, Tatyana; Sverdlov, Aleksey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The development of an effective and safe methods of conservative treatment of knee osteoarthritis of the has a priority in modern orthopaedics. Objective: to compare results of Platelet-Rich Plasma — PRP and PRP in combination with 2 % viscoelastic sodium hyaluronate gel (proFLEX INTRA) in patients with the II grade knee osteoarthritis. Methods: from 2018 to 2019 prospective randomized comparative study of the efficiency of using PRP therapy (group I) and PRP in combination with a 2 % viscoelastic sodium hyaluronate gel (proFLEX INTRA) (group II) was conducted in 50 patients with II grade knee osteoarthritis (aged between 48 and 73 years). Patients were assessed before treatment, 1, 3, and 6 months after treatment with the help of VAS while walking, WOMAC, and OKS scales. Laboratory assesment of inflammation markers in serum and synovial fluid were performed before treatment and 4 weeks after. Synovial fluid was examined by using clinical-microscopic and biochemical methods according to the following markers: cytosis, percentage of neutrophils, lymphocytes, synoviocytes and macrophages, protein, hyaluronic acid. In blood serum were determined: total protein, glycoproteins, chondroitin sulfates, alkaline phosphatase activity. Results: in II group was noted a statistically significant improvement according to VAS and WOMAC scale comparing with I group 6 months after treatment. The content of glycoproteins and chondroitin sulfates in blood serum of patients in the II group, also the protein content in synovial fluid, 4 weeks after treatment was lower (p < 0.05) comparing with the I group. However, the content of HA was higher (p < 0.05) in the II group of patients. Conclusions: both methods, PRP; PRP and HA allowed to reduce VAS pain score while walking and to improve joint function according to WOMAC and OKS scales in patients with the II stage knee osteoarthritis, six months after treatment. While, in the group of combined use PRP and 2 % viscoelastic sodium hyaluronate gel the results of treatment according to VAS and WOMAC scales were statistically significantly better and the inflammatory-dystrophic degree of changes in the knee was less comparing with the I group.